Bacterial Profile of Diabetic Foot Ulcer with duration and Types of Diabetes and Antibiotic Therapy - Syed Hasnain Ali Shah, Abdul Shakoor, Rukhsana Saboor, Aimen Mahmood Shah, Muhammad Salman Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find out the gram negative bacteria causing the diabetic foot ulcers and most effective antibiotic therapy. Study Design: Cross-sectional descriptive study Place and Duration of Study: Diabetic Center Hayatabad, Kabir Medical College Peshawar from 1st September 2021 to 28th February 2022. Methodology: Sixty nine admitted patients for the treatment of diabetes having type 1 diabetes mellitus and type 2 diabetes mellitus were enrolled. All the patients were on treatment of antibiotic such as gentacin, augmentin, amikacin and clindamycin. The specimens were analyze in microbiology laboratory and extracted by needle aspiration of material from the infected site and inoculate within 1hour after collection using gram staining smear for the detection or cytology of bacteria and its presence and absence in a specimens, for the isolation specimens were plated onto chocolate, phenyl ethyl alcohol (PEA) and MacConkey agar plate. To check the antibiotic susceptibility pattern Kirby Bauer test was performed. Results: There were eight anaerobic gram negative bacteria included in the study. In type 1 diabetes the Escherichia coli extended-spectrum-β-lactamase (ESBL) was 4.8% while in type 2 it was 95.2% in case of Klebsiella oxytoca. There is no bacteria in type1 while in type2, 100% were detected among 13 samples out of 69. E. coli (ESBL) was found in 66.7% in diabetic patients >10 years with foot ulcers while 33.3% in <5 years and Klebsiella oxytoca was 61.5% in >10 years while in <5 years, 23.1% was found in the lesions. In the wound all the presence of E. coli (ESBL) was high as compared to other gram negative bacteria. In antibiotic therapy E. coli was 76.2% were resistant while in Klebsiella oxytoca 69.2% were show resistant while 23.1 % were sensitive while Enterobacter was 100 % and Proteus mirabillus has 50.0% sensitivity. Serratia was 75% resistant and E. colicephalosporin producer were 77.8% resistant to augmentin. The sensitivity of clindamycin was zero percent in all gram negative bacteria. Amikacin is 90.5% sensitive to E-coli and 9.5% resistant while gentacin is 66.7% sensitive and 33.3% resistant to bacteria e-coli. Conclusions: Escherichia coli extended-spectrum-β-lactamase was found to be the most common gram negative bacteria detected in wound of diabetic foot ulcers.